Maternal Education and Nutritional Compliance among Mothers of Under-Five in Abeokuta, Ogun State: Implications for Social Work Practice​ - Ajibola Ishola; Ajiboye Oyeleke (Journal of Social Work Education and Practice, 2023)
This study investigated the influence of maternal education on nutritional compliance among mothers of under-five in some selected Hospitals in Abeokuta, Ogun State. The study was a descriptive survey design carried out at the Federal Medical Centre, Abeokuta; General hospital, Sokenu-Ijaye - Abeokuta; Sacred Heart Catholic Hospital, Lantoro; Olikoye Ransome Kuti Memorial Hospital, Asero and General Hospital, Odeda. Three hundred (300) mothers whose children are under five years old were conveniently sampled on their children immunization day. Data was collected using a self-structured questionnaire. The result revealed that there was a significant association between education and nutritional knowledge (X2 (3) = 66.76, p< 0.05). Education was also associated with nutritional compliance behaviour among mothers (X2 (3) = 11.02, p< 0.05) while the level of nutritional knowledge was significantly associated with nutritional compliance behaviour among mothers (X2 (1) = 6.76, p< 0.05). It was concluded that nutritional knowledge and education significantly influence nutritional compliance among mothers of under-five and necessary recommendations were made. Its implications for social work practice was also discussed.